Fertilizer use in Indonesian oil palm smallholder systems: agronomic and socio-economic constraints and opportunities - Rosanne E. de Vos; Ya Li Lim; Sunawan; Christopher R. Donough; Juan Pablo Monzon; Fatima A. Tenorio; Hendra Sugianto; Sandri Palupi; Antonius P. Tito; Shofia Saleh; Nadib Ulfaria; Joni Amsar; et al. (Environment, Development and Sustainability, 2026)
Oil palm smallholders in Indonesia use low amounts of fertilizer, leading to nutrient deficiencies and low yields and profits. This study examines the reasons for limited fertilizer use to identify opportunities for improving fertilizer management. This is vital to support smallholder livelihoods and to reduce the need to clear new land for oil palm cultivation. We explored agronomic and socio-economic factors influencing fertilizer use in oil palm smallholder fields in Indonesia. Methods included farmer diaries ( n = 958 fields), surveys, and in-depth interviews ( n = 44), conducted across six oil palm regions in Indonesia over three years (Jan 2020–Dec 2022). We used these data to calculate a nutrient score relative to attainable yield, and to identify enabling and constraining factors for implementing good fertilizer management. We found that half of the smallholders did not apply fertilizer, while the rest applied low doses and achieved low nutrient scores. Factors explaining low fertilizer use included financial constraints, limited fertilizer availability, and logistical issues. We show that, despite potential negative consequences for future yields and income, smallholders postponed fertilizer application in response to high fertilizer prices. Conversely, this study indicates that farmers who had access to credit, via oil palm collectors and/or farmer groups, used more fertilizer, and achieved higher nutrient scores. Enhancing fertilizer use among oil palm smallholders to prevent yield decline and income loss requires policy interventions to increase knowledge of sustainable fertilizer management among smallholders and fertilizer suppliers, as well as measures to facilitate access to credit, and ensure the timely availability of good-quality fertilizer.

Improving yield and profit in smallholder oil palm fields through better agronomy - Hendra Sugianto; Christopher R. Donough; Juan P. Monzon; Sunawan; Iput Pradiko; Ya Li Lim; Fatima A. Tenorio; Gonzalo Rizzo; Suroso Rahutomo; Fahmuddin Agus; Setiari Marwanto; Maja Slingerland; et al. (Agricultural Systems, 2025)

First things first: Widespread nutrient deficiencies limit yields in smallholder oil palm fields - Hendra Sugianto; Juan P. Monzon; Iput Pradiko; Fatima A. Tenorio; Ya Li Lim; Christopher R. Donough; Sunawan; Suroso Rahutomo; Fahmuddin Agus; James Cock; Joni Amsar; Rana Farrasati; et al. (Agricultural Systems, 2023)